A combined lens design for an LED low-beam motorcycle headlight. (May 2018) - Luo, D; Ge, P; Liu, D; Wang, H
A conventional low-beam projector headlight design for a motorcycle conventionally uses a combination of an elliptical reflector and a baffle plate. A clear cut-off line is formed by the baffle plate. Since only one freeform surface is used, the dispersion phenomena will occur with a white LED light source because the blue and yellow light is mixed unevenly. This leads to a high colour temperature. Another method uses a micro-lens array to solve the colour temperature problems. Without using the baffle plate, it is difficult to form a clear cut-off line. What's more, the freeform surface of the lens is complex and difficult to fabricate. We propose a combined lens, which uses a double freeform surface lens combined with a single freeform surface lens. In the combined lens, the double freeform surface lens is designed to solve the colour temperature drift and the single freeform surface lens is designed to solve the problem of the cut-off line. The simulation results can meet the ECE Regulation R113 revision 2(Class B) of the motorcycle low-beam.